(3GdCMGOjK GdeGFI GdeTJedI Ydi eGFI fSHI Edi GdUfGFYs - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3hHYO agPG JYdjb SejJg ebUO GdWGdH GdMKjK ai fXe eYfi GdGMGOjK hgG GfG GhQO GdGMGOjK GhdkG Ke GJHY cdkG efgeG HfXe eYfGg s
(3BNQgG (B:s
(3cCRhGL GdfHi Udi Gddg Ydjg hSde hChdGO GdegGLQjf hGdGfUGQ QVi Gddg Yfge hcPdc WGdH GdYde hGdhGYX GdPi jYX GdfGS HGdMK hGdPi jYdege GfJgi s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3GdfSNI HgG JdhjK s
Keywords: (3GdMOjK h GdeUWdMs